Qualidade do cuidado em instituições de longa permanência para idosos: criação e validação de instrumento de autoavaliação - Bruno Luís de Carvalho Vieira (2022)
The future aging of the population will increase the need for better long-term care, which must be evaluated to generate the health and longevity of the elderly and influence the choice of long-term care institutions for the elderly (LTC). This is a methodological study divided into three phases. The objectives are to know the theories, elaborate and validate an instrument of self-assessment of quality of care in LTC. The first phase was a scoping review with the question: What theoretical models have been used to define and evaluate the quality of care offered to elderly people in LTC? A total of 1,209 articles were found, 80 separated for full reading and 21 included for final analysis. Most authors, 47%, used the multidimensional model, which defines several dimensions for the assessment, developed for institutionalized elderly people. The structure, process, and results model, used in the industry, was widely found. The person-centered theory, in which the quality perceived by the elderly reflects the quality received, and the work environment-centered theory, which relates the work process to quality, were seen in smaller numbers. There are few theoretical models to support the construction of indicators and evaluation models, which should preferably be used to better deepen and direct the evaluation of care. In the second phase of the study, an instrument for self-assessment of the quality of care in LTC was developed and validated, carried out between March and December 2021, in three stages. In the first, the construction of the instrument was carried out based on a multidimensional model of quality, as it is the most comprehensive, Brazilian legislation and bibliographic research. The dimensions used were environment, home, care, family and community involvement, work team and management. For each one, evaluation indicators were created. In the second, validation by the modified Delphi Technique was performed, by electronic means, with 10 experts, chosen by experience and affinity with the theme. For the indicator to be maintained, a minimum consensus of 75% was required. Each indicator was analyzed in terms of relevance for evaluating both the quality of the LTC and the corresponding dimension, the adequacy of objectives, the wording, and the evaluation scale. The experts were able to give writing suggestions and make comments. In the third, the instrument was evaluated by 10 managers for final validation. 29 of the 35 indicators divided into six dimensions remained. The third phase of the study consisted in the development of a technical product, a guide for the use of the instrument by the LTC coordinators. It can be concluded that the quality of care in LTC proved to be multidimensional, involving several subjects, varying according to time and culture. The instrument can be used to monitor and follow-up LTC actions, for constant progress in care, continuous improvement and qualification of health care and comparison between LTC.